Roles played by protein metabolism and myogenic progenitor cells in exercise-induced muscle hypertrophy and their relation to resistance training regimens - Ishii, N.; Oasawara, R.; Kobayashi, K.; Nakazato, K. (The Journal of Physical Fitness and Sports Medicine, 2012)
To learn the mechanisms underlying resistance exercise-induced muscle hypertrophy, recent studies on muscle protein metabolism and myogenic progenitor cells were reviewed. Numerous studies have suggested that activation of the translation process plays a major role in a resistance exercise-induced increase in muscle protein synthesis, and also in muscle hypertrophy after a prolonged period of training. Among regulators of the translational activity, the mTORC1 signaling pathway has been shown to be important, although the relation between its upstream regulation and exercise regimen remains unclear. In addition, the muscle satellite cells play a part, even if not indispensable, in exercise-induced muscle hypertrophy, by supplying muscle fibers with new myonuclei. Middle to high exercise intensity has been regarded as essential for gaining muscle mass, because it causes the recruitment of large motor units with fast, type II muscle fibers, which are readily hypertrophied through activation of mTORC1 signaling. However, several studies have shown that low-intensity resistance exercises with either large exercise volume or prolonged contraction time effectively activate protein synthesis and induce muscle hypertrophy. These findings suggest that various strategies are possible in exercise regimens, and exercise intensity is not necessarily a primary factor for gaining muscular size.